Aggressive males are more attractive to females and more likely to win contests in jumping spiders. (September 2021) - Kwek, Bernetta Zi Wei; Tan, Min; Yu, Long; Zhou, Wei; Chang, Chia-chen; Li, Daiqin
Abstract : Consistent interindividual differences in behaviour (i.e. personality) and intraindividual variability in behaviour (higher intraindividual variability means lower behavioural predictability) are common across animal taxa. However, how personality and behavioural predictability of males and females influence female mate choice and male–male competition remains poorly understood. Here, we investigated this in the jade jumping spider, Siler semiglaucus . After assessing the level of aggression (an individual's average aggression) and aggression predictability (the variability around average aggression within an individual) of both S. semiglaucus males and females, we performed female mate choice trials to test whether aggression and aggression predictability in females, males or both would affect female mate choice. We also conducted male contest trials to test whether male aggression or aggression predictability would influence the outcomes of male contests. We found that both females and males showed consistent interindividual differences in aggression, and aggressive spiders were more predictable than less aggressive ones. Despite a positive correlation between aggression and predictability, male aggression predicted female mate choice better than aggression predictability. Females showed a directional preference for aggressive males over docile males regardless of female aggression or male aggression predictability. Predictable aggressive males were also more likely to win contests. Our results suggest that both female mate choice and male–male competition favour males with high aggression, and thus total sexual selection that acts on male aggression may be reinforcing. These findings also highlight that male S. semiglaucus with a higher level of aggression may have better reproductive performance. Highlights: Animals exhibit individual variation in aggression and aggression predictability. Their importance in sexual selection, however, remains poorly understood. We addressed this issue in the jumping spider S. semiglaucus. Females show a directional, but no assortative, preference for aggressive males. Highly predictable aggressive spiders are more likely to win male contests.